Cell Differentiation and Development in Arabidopsis Are Associated with Changes in Histone Dynamics at the Single-Cell Level . Issue 12 (30th December 2014) - Rosa, Stefanie; Ntoukakis, Vardis; Ohmido, Nobuko; Pendle, Ali; Abranches, Rita; Shaw, Peter
Abstract : Histone mobility is regulated during development in Arabidopsis roots, being higher in the division zone and lower in stem cells and differentiated cells, mainly due to changes in histone acetylation. Abstract: The mechanism whereby the same genome can give rise to different cell types with different gene expression profiles is a fundamental problem in biology. Chromatin organization and dynamics have been shown to vary with altered gene expression in different cultured animal cell types, but there is little evidence yet from whole organisms linking chromatin dynamics with development. Here, we used both fluorescence recovery after photobleaching and two-photon photoactivation to show that in stem cells from Arabidopsis thaliana roots the mobility of the core histone H2B, as judged by exchange dynamics, is lower than in the surrounding cells of the meristem. However, as cells progress from meristematic to fully differentiated, core histones again become less mobile and more strongly bound to chromatin. We show that these transitions are largely mediated by changes in histone acetylation. We further show that altering histone acetylation levels, either in a mutant or by drug treatment, alters both the histone mobility and markers of development and differentiation. We propose that plant stem cells have relatively inactive chromatin, but they keep the potential to divide and differentiate into more dynamic states, and that these states are at least in part determined by histone acetylation levels.